Cellular requirements for tumor-specific immunity elicited by heat shock proteins: tumor rejection antigen gp96 primes CD8+ T cells in vivo. - Udono, H (1994)
Purified preparations of 96-kDa heat shock proteins (gp96) have been previously shown to elicit tumor-specific immunity to the tumor from which gp96 is obtained but not to antigenically distinct chemically induced tumors. The cellular requirements of gp96-elicited immunity have been examined. It is observed that depletion of CD8+, but not CD4+, T cells in the priming phase abrogates the immunity elicited by gp96. The CD8+ T cells elicited by immunization with gp96 are active at least up to 5 weeks after immunization. Depletion of macrophages by treatment of mice with carrageenan during the priming phase also results in loss of gp96-elicited immunity. In the effector phase, all three compartments, CD4+ and CD8+ T cells and macrophages, are required. Immunity elicited by whole irradiated tumor cells shows a different profile of cellular requirements. In contrast to immunization with gp96, depletion of CD4+, but not CD8+, T cells during priming with whole tumor cells abrogates tumor immunity. Further, ablation of macrophage function during priming or effector phases has no effect on tumor immunity elicited by whole cells. Our results suggest the existence of a macrophage-dependent and a macrophage-independent pathway of tumor immunity. Our observations also show that in spite of exogenous administration, vaccination with gp96 preparations elicits a CD8+ T-cell response in vivo, and it is therefore a useful method of vaccination against cancer and infectious diseases.